2006
DOI: 10.1080/15287390500227365
|View full text |Cite
|
Sign up to set email alerts
|

Biological Half-Life and Oxidative Stress Effects in Mice with Low-Level, Oral Exposure to Tritium

Abstract: Tritium ((3)H) may enter the environment from human activities, particularly at production, processing, or waste storage sites such as the Department of Energy's Savannah River Site, a former nuclear production facility in South Carolina. Understanding the dynamics and potential adverse effects of tritium in exposed organisms is critical to evaluating risks of tritium releases at such sites. Previous studies estimated the biological half-life of tritium in mice to be approximately 1.13 d; however, these labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Previous studies have found that tritium causes harmful effects in rodents at concentrations several orders of magnitude higher than those found at the tritium disposal site (Brooks et al, 1976;Carsten and Commerford, 1976;Gao et al, 2002;Yamamoto et al, 1995). In addition, results from a laboratory study where exposure concentrations were comparable to those of mice inhabiting the tritium disposal site indicated that the tritium burdens of mice at the disposal site are insufficient to induce oxidative stress (Kelsey-Wall et al, 2005). As an isotope of hydrogen, the metabolic pathways for tritiated water in organisms are the same as those for water.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have found that tritium causes harmful effects in rodents at concentrations several orders of magnitude higher than those found at the tritium disposal site (Brooks et al, 1976;Carsten and Commerford, 1976;Gao et al, 2002;Yamamoto et al, 1995). In addition, results from a laboratory study where exposure concentrations were comparable to those of mice inhabiting the tritium disposal site indicated that the tritium burdens of mice at the disposal site are insufficient to induce oxidative stress (Kelsey-Wall et al, 2005). As an isotope of hydrogen, the metabolic pathways for tritiated water in organisms are the same as those for water.…”
Section: Resultsmentioning
confidence: 93%
“…Because tritium does not bioconcentrate, and because tritium has a relatively short biological half-life (Kelsey-Wall et al, 2005), there should be a relationship between whole body tritium concentrations of exposed mice and the amount of tritium applied to their environment. With an increased availability due to irrigation with tritiated water, whole body tritium concentration of exposed mice should rise.…”
Section: Resultsmentioning
confidence: 99%
“…10 However, consensus on the RBE of tritium has not yet been reached. [15][16][17][18] The UK Advisory Group on Ionizing Radiation released a report suggesting that given the large number of radiobiology studies that focus on tritium, its RBE should be classified as a minimum of 2 and that 3 should be considered for safety. 19 Although the biological effects of high doses of tritium have been defined and genetic and specific tumor effects have been identified in animal models after long-term exposure, epidemiological investigations into the health risks associated with exposure to tritium are not yet publicly available.…”
Section: Discussionmentioning
confidence: 99%
“… 10 However, consensus on the RBE of tritium has not yet been reached. 15 - 18 The UK Advisory Group on Ionizing Radiation released a report suggesting that given the large number of radiobiology studies that focus on tritium, its RBE should be classified as a minimum of 2 and that 3 should be considered for safety. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Kulkarni et al found that mitochondrial mutant cells with mutations occurring at different mitochondrial DNA (mtDNA) sites exhibited distinct radio sensitivities to X-ray irradiation, which was related to diverse DNA damage responses triggered in the mitochondrial mutant cells [ 20 ]. Currently, many studies focus on nuclear DNA damage caused by tritium exposure [ 21 , 22 , 23 ], but the impact of mitochondrial function regulation on the biological effects of tritium radiation has not been reported.…”
Section: Introductionmentioning
confidence: 99%